EFFECTIVE AND SAFE PHARMACOTHERAPY TODAY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The rapid development of pharmaceutical chemistry, pharmacology and the pharmaceutical industry in recent years has led to an unprecedented expansion and growth of the pharmaceutical market. According to the latest data, today about 30000 (!) names of medicines are converted on the world pharmacological market. Therefore, the practitioner has an urgent task not only to remember the names of the above drugs, but also to use them correctly in everyday activities. In addition, the doctor will need to know the advantages and disadvantages of new drugs compared to old ones, the interaction of drugs in the body. The effective, safe use of drugs can be studied by a physician as a result of many years of experience and skilled practice. The WHO estimates that more than half of all medicines are misused, dispensed or sold, and half of all patients receiving medicines are taking them incorrectly. Over-use, under-use or misuse of drugs is wasting limited resources and widespread health threats.